Proposing subsidies for regenerative water management: the case of the Uberabinha basin, São Paulo/SP - Kakihara, Adriana Dorça; Silva, Luciano Abbamonte da; Silva, Luis Octavio de Faria e (Scientific Journal ANAP, 2025)
Objective – discuss the importance of making the requirement for vacating environmental protection areas of watercourses more flexible.Methodology – purposeful research based on document analysis and data collection from field visits.Originality – presents a win-win alternative for recovering surface runoff of rainwater in highly urbanized areas that does not require the removal of residents or the total demolition of leisure areas of buildings.Results – less bureaucracy and greater agility in effectively clearing the surface course of streams.Theoretical contributions – prioritize the regenerative systemic vision in confrontation with environmental legislation in the recovery of the environmental functions of intensely urbanized valley bottoms; use the dejudicialization law as a tool for resolving environmental conflicts: ownership and dimensions to be vacated over underground channeled streams.Social and environmental contributions – eliminates the risk to lives, restores part of the stream’s original drainage capacity and enables future implementation of Nature-Based Solutions to reconnect the stream to the city and foster ecosystem services.
Keywords: Urban Resilience; Nature-Based Solutions; Sustainable Drainage